Detection of Cutaneouse Leishmaniasis species via PCR in Salah Adeen and Baghdad provences - Maysaa Ibrahim Al-Jubori; Abd Alrahman A. Al-Tae; Mohammad A. Al-Faham (Tikrit Journal of Pure Science, 2019)
Background: Leishmaniasis is a parasitic diseases that are spread worldwide due to various species of Leishmania, which are infect mammales diversity as well as human. L. tropica,    L. major, and L. aethiopica which is common causes of cutaneous Leishmaniasis in Salah Adeen and Baghdad provences.